Advantages of the Phosphatidylserine-Recognizing Peptide PSP1 for Molecular Imaging of Tumor Apoptosis Compared with Annexin V - Kim, Soyoun; Bae, Sang Mun; Seo, Junyoung; Cha, Kiweon; Piao, Meilan; Kim, Sun-Ji; Son, Hye-Nam; Park, Rang-Woon; Lee, Byung-Heon; Kim, In-San (PUBLIC LIBRARY SCIENCE, 2015)
A number of peptide-based indicators have been identified and reported as potential apoptosis probes, offering great promise for early assessment of therapeutic efficacy in several types of cancer. Direct comparison of the newly developed probes with previously used ones would be an important step in assessing possible applications. Here, we compared the newly identified peptide-based phosphatidylserine (PS) indicator PSP1 (CLSYYPSYC) with annexin V, a common probe for molecular imaging of apoptotic cells, with respect to PS binding kinetics, apoptotic cell-targeting ability, and the efficacy of homing to apoptotic tumor cells in a mouse model after treatment with the anticancer agent camptothecin. Our results indicate that PSP1 efficiently targeted apoptotic cells and generated apoptosis/tumor-specific signals after cancer treatment in the animal model, whereas a similar dose of annexin V showed weak signals. The formation of a stable complex of PSP1 with PS might be one reason for the efficient in vivo targeting. We suggest that PSP1 has potential advantages for in vivo apoptotic cell imaging and could serve as a platform for the development of de novo peptide-based probes for apoptosis.
Keywords: DE-NOVO PEPTIDE; STRUCTURE PREDICTION; CANCER; CELLS; EXPRESSION; DISCOVERY; CLEARANCE